The Permutational Composition

Algebra Level 5

Given f ( x ) = 3 x 2 + 1 x . f(x)=\frac{\sqrt{3x^2+1}}{x}. We define a positive algebraic function g g such that the composition f o g fog satisfies the equation r = 1 n ( f o g ( r ) ) 2 = n + 3 P n \prod_{r=1}^n (fog(r))^2=^{n+3}P_n for every positive integer n n . Find 4 g ( 4 ) 4g(4) .

This is one of my original problems. It belongs to the set- Questions I've Made © .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sandeep Bhardwaj
Jun 17, 2015

Using the given equation : r = 1 n ( f o g ( r ) ) 2 = n + 3 P n \displaystyle \prod_{r=1}^n (fog(r))^2=^{n+3}P_n

( f o g ( n ) ) 2 = r = 1 n ( f o g ( r ) ) 2 r = 1 n 1 ( f o g ( r ) ) 2 = n + 3 P n ( n 1 ) + 3 P n 1 (fog(n))^2=\dfrac{\displaystyle \prod_{r=1}^n (fog(r))^2}{\displaystyle \prod_{r=1}^{n-1} (fog(r))^2}=\dfrac{^{n+3}P_n}{^{(n-1)+3}P_{n-1}}

Putting n = 4 n=4 , we get :

( f o g ( 4 ) ) 2 = 7 P 4 6 P 3 = 7 (fog(4))^2=\dfrac{^7P_4}{^6P_3}=7

From the given definition of function : f ( x ) = 3 x 2 + 1 x f(x)=\dfrac{\sqrt{3x^2+1}}{x}

f o g ( 4 ) = 3 ( g ( 4 ) ) 2 + 1 g ( 4 ) fog(4)=\dfrac{\sqrt{3(g(4))^2+1}}{g(4)}

On squaring both sides, we will get :

( f o g ( 4 ) ) 2 = 3 ( g ( 4 ) ) 2 + 1 ( g ( 4 ) ) 2 (fog(4))^2=\dfrac{3(g(4))^2+1}{(g(4))^2}

7 = 3 ( g ( 4 ) ) 2 + 1 ( g ( 4 ) ) 2 \Rightarrow 7=\dfrac{3(g(4))^2+1}{(g(4))^2}

( g ( 4 ) ) 2 = 1 4 \Rightarrow (g(4))^2=\frac{1}{4}

g ( 4 ) = 1 2 or g ( 4 ) = 1 2 \Rightarrow g(4)=\dfrac{1}{2} \ \text{ or } \ g(4)=-\dfrac{1}{2}

  • g ( 4 ) = 1 2 g(4)=-\dfrac{1}{2} is neglected because g g is defined as a positive function.

Hence g ( 4 ) = 1 2 4 g ( 4 ) = 2 g(4)=\dfrac{1}{2} \Rightarrow 4g(4)=\boxed{2}

enjoy !

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...